Pancasila Sebagai Sumber Tertib Hukum Tertinggi (Suatu Kajian Filsafat): Pemahaman Bagi Mahasiswa UNJAYA, UNIMUGO dan UMK - Wirawan, Vani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
As a philosophical study, Pancasila is a conceptualization of living values in people's lives, where in this case one of the parts is realizing Pancasila as a source of law and order both in the life of the nation and state, namely in social relations between citizens and citizens, citizens and communities. country. This understanding program is a community service that is led by General Achmad Yani University Yogyakarta, Muhammadiyah University of Gombong and Muhammadiyah University of Kupang. This program aims to provide an understanding and strengthen the importance of understanding Pancasila as the source of the highest legal order in Indonesia (a philosophical study), through the Learning System method. With this, it is understood that Pancasila, in today's phenomenon, is only the main reference or legal basis for making all kinds of laws and regulations. However, the term Pancasila is no longer found as the source of all sources of law or legal order in all dimensions of national life. In particular, the legal system and modern legal scholars have been heavily influenced by the legal positivism school of thought, especially legism which only recognizes written regulations. For this reason, it is a mistake to not explain explicitly about Pancasila as the source of all sources of law.